2013
DOI: 10.25071/1705-1436.16
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Work and Workplace Injury Among Alberta Teens

Abstract: Utilizing a convenience sample of nearly 2000 respondents drawn fromadministrative data, this study finds 43.7 percentof adolescents (aged 12-14) and61.5 percent of young persons (aged 15-17) in the Canadian province of Albertareported employment in 2011/12. Of those employed,49.7 percent of adolescentsand 59.0 percent of young persons reported at leastone work-related injury inthe previous year. This study also identifies widespread non-reporting ofworkplace injuries and seemingly ineffective hazardidentifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Indeed, most commentary about young people and work raises concerns, particularly in terms of workplace health and safety (Hall et al, 2011; Runyan and Zakocs, 2000). For example, many studies have examined risk factors associated with young worker injury, suggesting that inadequate training, job type and power imbalances make young workers more vulnerable to injury than older workers (Barnetson, 2013; Breslin and Smith 2005; Cohen, 2013; Runyan and Zakocs, 2000). Some of the research on this issue points to how neo-liberal cutbacks (Cohen, 2013) and individualization of responsibility may lead young workers to feel uncomfortable raising safety concerns at work.…”
Section: Young Workers In the Global Northmentioning
confidence: 99%
“…Indeed, most commentary about young people and work raises concerns, particularly in terms of workplace health and safety (Hall et al, 2011; Runyan and Zakocs, 2000). For example, many studies have examined risk factors associated with young worker injury, suggesting that inadequate training, job type and power imbalances make young workers more vulnerable to injury than older workers (Barnetson, 2013; Breslin and Smith 2005; Cohen, 2013; Runyan and Zakocs, 2000). Some of the research on this issue points to how neo-liberal cutbacks (Cohen, 2013) and individualization of responsibility may lead young workers to feel uncomfortable raising safety concerns at work.…”
Section: Young Workers In the Global Northmentioning
confidence: 99%
“…Our research is informed by political economy (PE), 53 a framework that contributes to understanding why different stakeholders benefit differently. 53 , 54 A PE lens recognizes the influence, on micro-level experiences, of broader systemic factors, including the rules governing prevention and compensation systems, which are in turn shaped by the power dynamics and interests of the state, employers, and workers, as well as broader political and macro-economic conditions. 54 57 Applying a PE lens, we sought to uncover inequities within political and economic systems, and reveal how policies (e.g., labour market and social welfare) influence and shape the experiences of precarious employment and resulting health inequities among our research participants.…”
Section: Methodsmentioning
confidence: 99%
“…The development of OHS research on precarious work contexts and social inequalities in health over the last two decades has shown that certain categories of workers are exposed to a greater risk of sustaining occupational injuries and experiencing various obstacles related to the declaration of an injury, coverage by a third-party payer, and the rehabilitation and return-to-work (RTW) processes [73][74][75]. Workers in vulnerable situations are more often those with precarious employment status that offers little social protection and career prospects; temporary workers; or workers who are recent immigrants, racialised, or temporary foreign workers [6,[76][77][78][79][80].…”
Section: The Effect Of Paradoxes and Double Binds On Certain Categori...mentioning
confidence: 99%